Reversible uniaxial strain tuning in atomically thin WSe2. (15th June 2016) - Schmidt, Robert; Niehues, Iris; Schneider, Robert; Drüppel, Matthias; Deilmann, Thorsten; Rohlfing, Michael; de Vasconcellos, Steffen Michaelis; Castellanos-Gomez, Andres; Bratschitsch, Rudolf
Abstract: Due to their unique band structure, single layers of transition metal dichalcogenides are promising for new atomic-scale physics and devices. It has been shown that the band structure and the excitonic transitions can be tuned by straining the material. Recently, the discovery of single-photon emission from localized excitons has put monolayer WSe2 in the spotlight. The localized light emitters might be related to local strain potentials in the monolayer. Here, we measure strain-dependent energy shifts for the A, B, C, and D excitons for uniaxial tensile strain up to 1.4% in monolayer WSe2 by performing absorption measurements. A gauge factor of − 54 meV %, − 50 meV %, + 17 meV %, and − 22 meV % is derived for the A, B, C, and D exciton, respectively. These values are in good agreement with ab initio GW-BSE calculations. Furthermore, we examine the spatial strain distribution in the WSe2 monolayer at different applied strain levels. We find that the size of the monolayer is crucial for an efficient transfer of strain from the substrate to the monolayer.